Towards a rapid immuno-test for tuberculosis: Immunochemical characterisation of a suitable mycolic acid antigen preparation - Verschoor, Jan Adrianus (University of Pretoria, 2020)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2020.